[1 supra 3 + 1 supra 3 :(1-1 supra 3)]: 3 supra 2
Vă rog
Răspunsuri la întrebare
Răspuns de
3
[1 supra 3 + 1 supra 3 :(1-1 supra 3)]: 3 supra 2=
=[1/3 +(1/3):(1- 1/3)]:(3/2)=
=[1/3 +(1/3):(2/3)]x(2/3)=
=[1/3 +(1/3)x(3/2)]x(2/3)=
=[1/3 +1/2]x(2/3)=
=(2/6 +3/6)x(2/3)=
=(5/6)x(2/3)=10/18=5/9
=[1/3 +(1/3):(1- 1/3)]:(3/2)=
=[1/3 +(1/3):(2/3)]x(2/3)=
=[1/3 +(1/3)x(3/2)]x(2/3)=
=[1/3 +1/2]x(2/3)=
=(2/6 +3/6)x(2/3)=
=(5/6)x(2/3)=10/18=5/9
Alte întrebări interesante
Matematică,
8 ani în urmă
Biologie,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Alte limbi străine,
9 ani în urmă